The sun god and the savior: the Christianization of the Nahua and Totonac in the Sierra Norte de Puebla, Mexico - Stresser-Péan, Guy, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2009)
This translation presents two decades of fieldwork in the Sierra Norte de Puebla, Mexico, where native pre-Hispanic pagan beliefs blended with traditional Catholic evangelization from the 16th century and the more recent intrusion of modernism.
Converting the Indians in sixteenth-century Central Mexico to Christianity -- From spiritual conquest to parish administration in colonial Central Mexico -- A trilingual, traditionalist indigenous area in the Sierra Norte de Puebla -- Introduction of Christianity in the Sierra Norte de Puebla -- Local religious crises in the sixteenth and seventeenth centuries -- The Tutotepec Otomí Rebellion, 1766-1769 -- Contemporary traditions in the Sierra Norte de Puebla -- Sacred drums, Teponaztli, and idols from the Sierra Norte de Puebla -- Traditional indigenous festivities in the Sierra Norte de Puebla -- Elements and accessories of traditional native ceremonies -- Christian festivities in the villages of the Sierra Norte de Puebla -- Dances that originated in the pre-Hispanic period -- Dances that originated during the colonial period -- Holders of indigenous wisdom -- Relics of the Mesoamerican calendar in the Sierra Norte de Puebla -- Beliefs about the formation and the end of the world -- Cosmology: the world in the eyes of the Indians of the Sierra Norte de Puebla -- The souls of beings and things -- Supernatural beings in the beliefs and religious practices of Indians in the Sierra Norte de Puebla -- The non-syncretic religion of the last Nahuas of Central Mexico -- Religious syncretism among today's Indians in the Sierra Norte de Puebla.
Keywords: Nahuas -- Mexico -- Puebla (State) -- Religion; Nahuas -- Missions -- Mexico -- Puebla (State); Nahuas -- Mexico -- Puebla (State) -- Rites and ceremonies; Totonac Indians -- Mexico -- Puebla (State) -- Religion; Totonac Indians -- Missions -- Mexico -- Puebla (State); Totonac Indians -- Mexico -- Puebla (State) -- Rites and ceremonies; Christianity and culture -- Mexico -- Puebla (State); Christianity and other religions -- Mexico -- Puebla (State); Syncretism (Religion) -- Mexico -- Puebla (State); Puebla (Mexico : State) -- Religious life and customs; Puebla (Mexico : State) -- Social life and customs; Stresser-Péan, Claude. Fete du maïs